Late Neurological Syndrome That Developed After Carbon Monoxide Intoxication a Case Report - Doğan, Kamil Hakan; Özbek, Seda; Doğan, Nadire Ünver; Karabulut, Ahmet Kağan (The Bulletin of Legal Medicine, 2014)
Carbon monoxide (CO) is a colorless, odorless, and non-irritant gas occurring as a product of incomplete combustion and it is lighter than air. Intoxication with this gas is usually seen during the winter months depending on unsuitable chimney stoves or heaters burned as charcoal in a closed environment. CO intoxication is a serious condition, it can result in death or severe neurological disorders. In rare cases of CO intoxication, after the short-term recovery period after acute treatment, late neurological syndrome may develop. In this syndrome, a variety of neurological and/or psychiatric symptoms accompanied by hyperintense lesions in the subcortical white matter especially in the basal ganglia in typical cranial computed tomography and magnetic resonance imaging (MRI) are observed. Prognosis of patients is closely associated with white matter lesions on brain MRI. In this study, the presence of periventricular hyperintensity on T2-weighted images in cranial MRI as late neurological syndrome sign that developed after carbon monoxide intoxication in a 65 year old female patient is presented. It is known that CO poisoning has serious harms in the acute period. In these cases it should be kept in mind that, as defined in our case, late neurological syndrome symptoms may occur after about a month from intoxication. Therefore, regular follow-up of patients should be performed and they need to be re-evaluated in terms of forensic reports. Keywords: Carbon monoxide, neurology, forensic medicine, imaging.